Analiza frezalnih parametrov pri obdelavi poliuretanskih pen - Hafner, Rok (visokošolska dela, 2020)
This doctoral thesis presents the possibility of machining of rigid polyurethane foams in the protection of cultural heritage field. In addition to the artistic aspect of quality, the product lifetime represents an extremely important property, which is determined by the adhesion strength of the primary protective layer. The rigid polyurethane foams of certain densities were used on the basis of empirical aspects so far. Optimization of surface treatment was experimentally determined based on the adhesion tests of the primary layer. The characterization of the treated surfaces is carried out as a basis for determining the milling parameters. Key parameters of roughness are determined with the actual effect on the adhesion of the coating. The results of the comparison of different polyurethane foam densities reversed the expectations that the greater roughness of the surface represents a better adhesive strength of the coating. An empirical model for milling parameters was installed at different foam density, which eliminates the adhesion measurement process
Keywords: adhezija nanosa; areal surface topography; coat adhesion; disertacije; dissertations; empirical modelling; empirično modeliranje; frezanje; kakovost obdelane površine; metodologija odziva površin; milling; polyurethane modelling foam; response surface methodology; technological process parameters; tehnološki parametri procesa; toga poliuretanska pena